New genera, species and records of Maeridae from Australian Waters: Austromaera, Ceradocus, Glossomaera, Hamimaera, Huonella gen. nov., Linguimaera and Maeraceterus gen. nov. (Crustacea: Amphipoda) - Hughes, Lauren E. (Zootaxa, 2016)
Thirty species of Maeridae are reported for Australian waters including the description of two new genera and nine new species. The new genus Huonella from southern Tasmanian seamounts is distinguished among the maerids by characters on the uropod 3, including elongation of both rami, inner ramus half the length of the outer ramus and outer ramus two articulate. The new genus Maeraceterus is establish for two new species, M. bramblensis from Western Australia and M. taaroa from Norfolk Island, which have a near transverse gnathopod 1 propodus palm and symmetrical male gnathopod 2. The new species Ceradocus baudini, Hamimaera thijsseni, Linguimaera boeckoides, L. daveyi, L. everardensis and L. mere are described here in. Additional distribution records are provided for eleven known Ceradocus and seven known Linguimaera, as well as three known maerids Austromaera mastersii (Haswell, 1879a), Glossomaera octodens (Sivaprakasam, 1969) and Hamimaera hamigera (Haswell, 1879b). Collections reported on here include material from Australia; Cocos (Keeling) and Christmas Islands, Indian Ocean; the Torres Strait; Papua New Guinea, Bismarck Sea and Norfolk Island, South Pacific. Keys to Ceradocus and Linguimaera sensu lato species in Australian waters are provided.